Problems Faced by Rural Area Students at Madrasah Tsanawiyah in Learning English Speaking - Zarah Amelia; Sriati Usman; Abdul Kamaruddin; Wahyudin Wahyudin (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the process of acquiring English speaking skills, emphasizing the indispensable role of grammar, vocabulary, and pronunciation in facilitating effective communication between speakers and listeners. Acknowledging the critical need for learners to command these core components of the English language, this research specifically targets students residing in rural locales. Utilizing a qualitative methodology, the investigation centred on eighth-grade students from a Private Madrasah Tsanawiyah, chosen via convenience sampling. Data were garnered through observations, interviews, and questionnaires, revealing that issues related to practical application of skills were more pronounced than theoretical knowledge gaps. Notably, the findings indicate that a lack of confidence significantly impedes skill development, with 80% of challenges linked to this factor, compared to 72% associated with knowledge deficiencies in language production. In light of these insights, the research underscores the paramount problem of inadequate skill factors among students. Consequently, it advocates for English teachers to exhibit superior pedagogical competence, highlighting the necessity for educators to deploy effective teaching methodologies within the instructional framework.